Mitral annulus disjunction: is it a marker of ominous prognosis?. (8th February 2021) - Cunha, NPD; Rigueira, J; Santos, R; Nunes-Ferreira, A; Rodrigues, T; Antonio, P; Pereira, S; Morais, P; Silva, P; Brito, J; Silva, B; Placido, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Mitral annulus disjunction (MAD) has been proposed as a contributing factor for arrythmias and mitral regurgitation in patients with mitral valve prolapse (MVP), however its clinical relevance is still under investigation. Objective: To evaluate the frequency of MAD in MVP patients, to characterize clinically patients with MAD and assess potential markers for events. Methods: Single-center retrospective study of consecutive patients with MVP documented in transthoracic echocardiogram between January 2014 and October 2019. MVP was defined according to the 2017 AHA recommendations; MAD was defined as a separation between mitral valve annulus and the left ventricle free wall. Demographic, clinical, echocardiographic, electrocardiographic data were collected. The results were obtained using Chi-square and Mann-Whitney tests; logistic regression was used to find predictors of events. Results: 247 patients were included (mean age 62.9 ± 18 years, 61% males), of these 23 (9.3%) had MAD (mean age 56 ± 20 years, 56.5% males). The maximum diameter of MAD was 10 ± 3mm (range 5-18). 21 patients (92.3%) had mitral regurgitation, and it was at least of moderate severity in 65.2% of patients. Most of the patients (91.3, n = 21) were in sinus rhythm (SR). During follow-up (FUP) of 29 ± 19 months, 39% (n = 9) of the patients developed symptoms, 22% (n = 5) had atrial fibrillation (AF), 4.3% (n = 1) had acute aortic syndrome (AAS), 4.3% (n = 1) needed ICD, 22% (n = 5) were submitted to mitral valve intervention, 8.7% (n = 2) were admitted to hospital and 8.7% (n = 2) died. None of the patients presented sustained ventricular arrhythmias (SVA) as assessed in regular Holter monitoring. These patients had more AAS and needed more ICD in FUP compared to patients without MAD (p = 0.007 and p = 0.006, respectively) Mitral cord rupture (p = 0.04), age (p = 0.044), maximum velocity of tricuspid regurgitation (p = 0.04) and IVS thickness (p = 0.017) were associated with AF in MAD patients. in univariate analysis, interventricular septum thickness was a predictor of AF in this subgroup (OR 4.0, 95%CI 1.1-14.3, p = 0-032) The presence of SR was associated with survival (p = 0.03). There were no predictors of hospital admission or mitral intervention. Conclusion: Patients with MAD had a relatively benign prognosis with few events during follow-up, although with more AAS and ICD in FUP. In our sample, AF was more common than SVA. Left ventricle hypertrophy was a predictor of AF and sinus rhythm was associated with survival. Larger studies with more patients and other methods of imaging are needed to confirm our results.